Titel prent: Duwen naar den verkeerden kant : de arbeider: "Zoolang jij duwt naar den kant van de brandkast..." - Hahn, Albert
Titel prent: Duwen naar den verkeerden kant : de arbeider: "Zoolang jij duwt naar den kant van de brandkast...".